2015
DOI: 10.1090/s0002-9939-2015-12436-7
|View full text |Cite
|
Sign up to set email alerts
|

Groups of unitary composition operators on Hardy-Smirnov spaces

Abstract: Let Ω be an open simply connected proper subset of the complex plane. We identify, up to isomorphism, which groups are possible for the group of unitary composition operators of a Hardy-Smirnov space defined on Ω. We also study the relationship between the geometry of Ω and the corresponding group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…∈ Ω to determine which symbols Φ and Ψ induce Hermitian and unitary composition operators, respectively (see, for instance, [1,5,17,18]). Here we shall introduce a different approach.…”
Section: Hermitian and Unitary Composition Operatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…∈ Ω to determine which symbols Φ and Ψ induce Hermitian and unitary composition operators, respectively (see, for instance, [1,5,17,18]). Here we shall introduce a different approach.…”
Section: Hermitian and Unitary Composition Operatorsmentioning
confidence: 99%
“…For the case of normal operators (see [25,Theorem 5.1.15]), composition operators on H 2 (U) are induced by Φ(z) = λz with |λ| ≤ 1. The characterization of unitary composition operators on Hardy-Smirnov spaces was given by Gunatillake, Jovovic and Smith in [18,Theorem 3.2]: C Φ is a unitary bounded composition operator on H 2 (Ω) if, and only if, there are complex numbers λ and r with |λ| = 1 such that Φ(z) = λz + r is an automorphism of Ω. The case of Hermitian composition operators on H 2 (Ω) was studied by Gunatillake in [17,Theorem 3.3], where it was shown that if C Φ is a Hermitian bounded composition operator, then Φ(z) = λz + r for some real number λ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations